2014
DOI: 10.2149/tmh.2014-15
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Acanthamoeba Genotype T4 from a Non-Contact Lens Wearer from the Philippines

Abstract: We report the case of a 76-year old Filipino male who presented with pain, redness, and blurring of vision of the right eye. Corneal scraping was done and sent to the St. Luke’s Research and Biotechnology Group for detection and identification of the infectious agent. Morphological detection was performed by allowing the organism from the scraping to grow in 1.5% non-nutrient agar plate with heat-killed E. coli. Trophozoites with acanthopodia and double-walled cysts characteristic of Acanthamoeba were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…However, the disease has also been reported in non-contact lens wearers [18,26,27]. This further affirms the possible contamination through direct contact to contaminated water and soil.…”
Section: Epidemiology Of Acanthamoeba In Aseanssupporting
confidence: 70%
See 1 more Smart Citation
“…However, the disease has also been reported in non-contact lens wearers [18,26,27]. This further affirms the possible contamination through direct contact to contaminated water and soil.…”
Section: Epidemiology Of Acanthamoeba In Aseanssupporting
confidence: 70%
“…[24]. Acanthamoeba-infected individuals can also be a source of the isolates of organism through sinuses, brain and corneal and skin specimens [22,[25][26][27] and even in necrotic tissues [18].…”
Section: Epidemiology Of Acanthamoeba In Aseansmentioning
confidence: 99%
“…In addition, it is important to Sharma et al 2004;Zhang et al 2004;Spanakos et al 2006;Ertabaklar et al 2007;Ozkoc et al 2008;Booton et al 2009;Iovieno et al 2010;Nagyová et al 2010b;Niyyati et al 2010;Nuprasert et al 2010;Lorenzo-Morales el al. 2011;Arnalich-Montiel et al 2013b;Duarte et al 2013;Buerano et al 2014;Ghamilouie et al 2014a, b a;Ghamilouie et al 2014a, b b;Behera et al 2016;Padzik et al 2016;Tawfeek et al 2016;Alves et al 2018;Buchele et al 2018;Fabres et al 2018;Taher et al 2018;Bahreini et al 2019 note that in the cases described in this systematic review, the genotypes T1, T6, T14, T16, T17, T18, T19, T20, T21, and T22 were not found causing AK.…”
Section: Resultsmentioning
confidence: 72%
“…The occurrence of FLA in treated water cannot be neglected due to the increasing reports of keratitis in Malaysia [ 56 ], Indonesia [ 57 ], and the Philippines [ 58 ]. Keratitis had always been associated with the infection caused by Acanthamoeba , but Hartmannella (= Vermamoeba ) too, is able to cause similar symptoms of watery eyes, redness and blurred vision [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%